FeO-based nanostructures and nanohybrids for photoelectrochemical water splitting. (May 2020) - Kment, Š.; Sivula, K.; Naldoni, A.; Sarmah, S.P.; Kmentová, H.; Kulkarni, M.; Rambabu, Y.; Schmuki, P.; Zbořil, R.
Abstract: The need to satisfy the growing global population's enormous energy demands is a major challenge for modern societies. Photoelectrochemical (PEC) water splitting (WS) is seen as a leading strategy for producing an extremely promising renewable store of energy – hydrogen (H2 ). However, PEC-WS is a complex process involving several sequential physicochemical reaction steps including light absorption, separation of photoexcited charges, and surface redox reactions. At present, FeO-based semiconductors represent a unique class of materials known to exhibit very high performance in all these processes. This review summarizes and critically discusses the major components of PEC-WS systems incorporating FeO-based light-harvesting systems, and outlines the progress that has been made, particularly over the last decade. Emphasis is placed on materials used as photoanodes (including hematite and nonhematite iron oxides, spinel iron ferrites, and pseudobrookite iron titanates) as well as materials used as cocatalysts and passivation layers – notably iron hydroxyoxides and their composites. We discuss strategies for overcoming the main limitations of the aforementioned materials via nanostructuring, elemental doping, surface decoration, and the formation of advanced hybrid nanoarchitectures. Finally, we use this knowledge to present a critical overview of the field and the future prospects of Fe-O semiconductors in PEC-WS applications.